A Study on Coffee Leaf Rust and Farmer’s Management Practices in Lalitpur District - Kafle, Shashank; Karki, Rojan (Nepalese Journal of Agricultural Sciences, 2025)
This study was conducted to assess coffee leaf rust (CLR) prevalence and farmers' management practices. Eighty farmers from five VDCs in Lalitpur were interviewed. The survey found diseases to be the primary issue for 60% of farmers, with CLR being the most damaging (80%). White stem borer infestations were also significant (91%). Thuladurlung had the highest disease incidence (71%), while Gimdi had the lowest (57.5%). The average disease intensity was 2.65 on a scale of 1-4, with Gimdi scoring the highest at 2.52 and Pyutar the lowest at 2.22. Most farmers (79%) used Bordeaux mixture, and 48% had received training on CLR. The study identified a lack of cultural practices, organic manure, essential nutrients, and biological control agents, and a need for more research on CLR in Nepal.